PELATIHAN KEGIATAN SENSORIAL TRAINING MONTESSORI UNTUK MAHASISWA DAN GURU PAUD - Rusdiani, Nurtina Irsad; Wulansari, Betty Yulia; Muttaqin, Muhammad Azzam; Katoningsih, Sri; Nuraini, Febitesna; Aulina, Choirun Nisak; Anisa, Clera Agretyas Nur; Saputri, Wahyu Dwi; Meythasharoh, Vera Putri (Universitas Pattimura, 2023)
The partner educational institution, namely the Ponorogo Early Education Center (Pocenter), has not yet implemented sensory stimulation in children because educators do not yet understand more deeply how Montessori sensorial training activities work. So far the teachers only provide normal sensorial activities and do not use Montessori sensorial training. Through this training activity, it is hoped that educators at Pocenter and students as prospective educators can implement it when they graduate. This activity is the result of collaboration between four PG-PAUD study programs at Muhammadiyah universities. The activity was carried out online with six virtual meetings and involved speakers from the University of Malaysia Sarawak. The results of the pretest and posttest can be concluded that this workshop influenced the mindset of workshop participants for center teachers and prospective PAUD teacher students positively and significantly. This can be seen in the α value being smaller than 0.05, namely 0.00 and the t value being negative, read as positive because the pretest value is lower than the posttest value.